Field emission enhancement of composite structure of ZnO quantum dots and CuO nanowires by Al2O3 transition layer optimization. Issue 10 (July 2020) - Sun, Lei; Chen, Enguo; Guo, Tailiang
Abstract: In this paper, ZnO quantum dots (QDs)-CuO nanowires (NWs) heterostructure was synthesized by a mild solution method. The Al2 O3 transition layer were deposited on CuO NWs by surface modification engineering using atomic layer deposition (ALD) to increase the nucleation probability of ZnO QDs. The field emission properties of the composites were investigated. The results reveal that the CuO@Al2 O3 /ZnO QDs ternary heterostructures have the turn-on field of 2.82 V/μm and the field emission enhancement factor of 5798, which are superior to that of ZnO QDs-CuO NWs and pure CuO NWs. The improvement of field emission performance is mainly attributed to the decrease of the electron transport barrier at the interface and the increase of the oxygen vacancies, making it easier to transport electrons to ZnO QDs. The use of amorphous Al2 O3 in the transition layer also effectively alleviates the lattice mismatch between ZnO QDs and the substrate. This study provides an effective method for enhancing the field emission performance of the core-shell nanomaterial device.